Nanotechnology for the theranostic opportunity of breast cancer lung metastasis: recent advancements and future challenges - Miao, Lin; Kang, Yue; Zhang, Xin Feng (Frontiers in Bioengineering and Biotechnology, 2024)
Lung metastasis of breast cancer is rapidly becoming a thorny problem in the treatment of patients with breast cancer and an obstacle to long-term survival. The main challenges of treatment are the absence of therapeutic targets and drug resistance, which promotes the development of nanotechnology in the diagnosis and treatment process. Taking advantage of the controllability and targeting of nanotechnology, drug-targeted delivery, controlled sustained release, multi-drug combination, improved drug efficacy, and reduced side effects can be realized in the process of the diagnosis and treatment of metastatic breast cancer(MBC). Several nanotechnology-based theranostic strategies have been investigated in breast cancer lung metastases(BCLM): targeted drug delivery, imaging analysis, immunotherapy, gene therapy, and multi-modality combined therapy, and some clinical applications are in the research phase. In this review, we present current nanotechnology-based diagnosis and treatment approaches for patients of incurable breast cancer with lung metastases, and we hope to be able to summarize more effective and promising nano-drug diagnosis and treatment systems that aim to improve the survival of patients with advanced MBC. We describe nanoplatform-based experimental studies and clinical trials targeting the tumor and the tumor microenvironment(TME) for BCLM to obtain more targeted treatment and in the future treatment steps for patients to provide a pioneering strategy.